A novel echocardiography formula for calculating predicted pulmonary vascular resistance in patients with mitral stenosis (Faculty of Medicine Universitas Indonesia, 2016)
Background: Pulmonary vascular resistance (PVR) plays an important role in the natural history, prognosis, and outcome after valve intervention in patients with mitral stenosis (MS). The existing formula to estimate PVR by means of echocardiography is not readily applicable in the MS patient subset because it does not specifically calculate the risk of PVR in MS. The aim of this study was to find a new echocardiography formula to estimate PVR in MS. Methods: This diagnostic study was conducted in 2 stages. In the first stage, 58 consecutive subjects with MS were studied to find some model formulas for estimating PVR by multiple regression. Eight echo parameters were analyzed to seek their correlation with the invasive PVR value as a gold standard. The formula that had the best correlation and was easiest to use would be selected. In the second stage, those model formulas were validated by applying them to a further 34 consecutive MS subjects. Results: Four formulas which gave a discriminator coefficient of r2 0.62–0.68 were derived. The best model formula was proposed for further application. The new selected formula PVR=-7.465+3.566 TRvmax –(0.23 TVs’)+6.799 (RV-MPI) showed good correlation (r=0.71, p<0.001) to the invasive PVR value, with good reliability. TRvmax is maximal velocity of tricuspid regurgitation, TVs’ is systolic velocity of tricuspid annulus, and RV-MPI is right ventricle index myocardial performance. ROC curve showed that the cut off point 7.2 has good sensitivity and specificity (90% and 88%, respectively) to predict PVR 7 WU. Conclusion: This study has shown that a novel echocardiography formula can estimate PVR with good correlation and reliability in subjects with mitral stenosis.